BISNIS DAN KONFLIK DI MEKSIKO - Randhi Satria (Universitas Wahid Hasyim Semarang, 2014)
The Conflict in Mexico rising in several years later becomes one of the most deadly conflicts on earth. The clash between drug cartels and the state police has took many lives. The government policy to take war on the cartels since Felipe Calderon took charge in 2006 which contributing for the escalation of conflict between the two parties. Clash between interests by cartels and the USA-Mexico government lead every party protecting their own interest from threat. To protect this, cartels armed them self with weapons which stronger than the Mexican government police and army weapon. With this condition bloody clash between parties unavoidable which lead Mexico in to the deadliest conflict against transnational organized crimes? The challenge concern about drug cartels seems very difficult since every party have interest especially about business. What is the USA national interest in Mexico and how do they protect the interest? What are Mexico government interest and also the interest of drug cartel in Mexico-USA border? This paper will discuss about the business and conflict in Mexico, especially since the war against drug cartels policy made by Calderon in 2006.